Novell(r)'s Guide to NetWare 6 Networks - F.Hughes Jeffrey (Wiley, 2002)
The book gives you over 1500 pages of comprehensive, logically organized coverage on NetWare 6 giving full details on installation, upgrading, eDirectory, troubleshooting, maintenance, security, administration and integration with other Novell products including clustering, Portal services, ZENworks, GroupWise, network protocols and configuration, BorderManager, I-chain and ICS. Novell's Guide to NetWare 6 Networks includes steps, hints, appendices with error codes and resolutions, console commands, debugger commands, product integration cross-references and a CD with an evaluation version of NetWare 6 -- truly all one needs to administer and maintain a NetWare network.